Clinical Presentation and Outcome in Children Admitted with Severe Malaria - Hussain, Niaz; Rayaz, Saima; Naziah; Akhtar, Arbab Nadeem; Hanif, Muhammad; Habib, Ghazala (Indus Journal of Bioscience Research, 2025)
Background: Malaria, caused by Plasmodium species, mainly affects African children, with P. falciparum being the deadliest strain. Severe cases lead to cerebral malaria, anemia, and organ dysfunction. Early diagnosis and artemisinin-based therapies improve outcomes, but healthcare limitations hinder effective management and treatment. Objectives: to examine the presentation features and laboratory profiles of severe malaria in children together with outcome tracking and mortality and morbidity predictive factors. The study findings will determine better treatment approaches to enhance patient care throughout malaria-endemic areas. Study design: A Retrospective Study. Place and duration of study. From December 2023 to May 2024 at Paediatrics Department Bolan Medical Complex Hospital Quetta. Methods: o n t h i s Descriptive Study that operated within a tertiary healthcare facility situated in an area with high rates of malaria. Medical staff reviewed admission records from patients under 15 years of age who received laboratory confirmation of severe malaria at the specified facility. Results: 136 children who had severe malaria received examination. The participant children had an average age of 5.2 years (standard deviation ± 2.8 years). The male-to-female ratio was 1.4:1. All patients manifested with fever during the study (100%) along with prostration in 82% of patients and severe anemia in 67% of patients and cerebral malaria in 48% of patients. Among the patients being studied 32 percent experienced respiratory distress symptoms. The laboratory analysis revealed mean results of 6.4 g/dL hemoglobin (SD ± 2.1, p = 0.03) with 4.6 mmol/L lactate (SD ± 1.9, p = 0.02) and 12.5% parasitemia (SD ± 5.6, p = 0.01). Conclusion: Severe malaria in children presents with anemia and neurological disorders. Despite treatment, high mortality persists, requiring better prevention and supportive care. Early diagnosis, artesunate therapy, and improved healthcare infrastructure can reduce disease burden and improve outcomes in endemic regions.